2008
DOI: 10.1016/j.nuclphysb.2008.04.031
|View full text |Cite
|
Sign up to set email alerts
|

CP observables with spin–spin correlations in chargino production

Abstract: We study the CP-violating terms of the spin-spin correlations in chargino production e + e − →χ ± 1χ ∓ 2 , and their subsequent two-body decays into sneutrinos plus leptons. We propose novel CP-sensitive observables with the help of T-odd products of the spin-spin terms. These terms depend on the polarizations of both charginos, with one polarization perpendicular to the production plane. We identify two classes of CP-sensitive observables; one requires the reconstruction of the production plane, the other not… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 53 publications
(67 reference statements)
0
12
0
Order By: Relevance
“…In the MSSM such a phase stems from the µ parameter or the soft breaking terms and enters through tan β-enhanced loop factors. B → Dτ ν complements collider studies of these phases [34].…”
Section: Discussionmentioning
confidence: 70%
“…In the MSSM such a phase stems from the µ parameter or the soft breaking terms and enters through tan β-enhanced loop factors. B → Dτ ν complements collider studies of these phases [34].…”
Section: Discussionmentioning
confidence: 70%
“…[11,21]. Typically their statistical significance is increased by ∼ 20% [11,18], compared to the asymmetries given in Eq. (20).…”
mentioning
confidence: 86%
“…Note that the neutralino and chargino decays will not yield additional CP-sensitive contributions, since these are twobody decays via scalar particles. The T-odd spin-spin correlation term f is analogous to the corresponding term in neutralino [11] or chargino [18] pair production at the ILC, since all these processes have the same kinematical structure.…”
Section: T-odd Observablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some previous studies of CP violation involving charginos may be found in Refs. [3,4,5,6,7,8,9,10,11].…”
mentioning
confidence: 99%